Imaging of skin thermal properties with estimation of ambient radiation temperature. - Otsuka, K. (IEEE Engineering in medicine and biology magazine)
Our latest system for the imaging of temperature and other thermal properties of the skin provides not only precise temperature distribution of the skin but also high-speed measurement of emissivity and inertia distribution. The method enabled us to measure the emissivity and thermal inertia of the skin even when the temperature distribution of the inner surface of the hood was not uniform. Two-dimensional measurement with hood switching, and a single-hood measurement system were considered.